UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA MATERI PERUBAHAN LINGKUNGAN MENGGUNAKAN STRATEGI INQUIRY DI KELAS IV MADRASAH IBTIDAIYAH MUHAMMADIYAH MIRI KECAMATAN POLOKARTO KABUPATEN SUKOHARJO TAHUN PELAJARAN 2023/2024 - Alfian Catur Syaukani,; Alfian Eko Rochmawan,; Sukari, Sukari (JOEL: Journal of Educational and Language Research, 2023)
In learning, appropriate methods are needed to convey material so that students more easily understand and digest the material presented, which basically will increase student learning outcomes. The position of a teacher in the world of education occupies the highest position, considering his role as the first person to convey information and knowledge to students consciously in learning. Not only in teaching and learning, a teacher also acts as a facilitator, mediator and motivator for students, and expertise or skills are needed in guiding, developing and managing learning activities so as to create an atmosphere of effective and efficient teaching and learning activities. To achieve success and the learning process, of course, a learning strategy is needed that is appropriate to the material and student character. Because in learning, appropriate methods are needed, especially in science learning related to nature systematically, so that in learning science, it is not only mastery of knowledge, but also requires concepts and facts and principles which are a process of discovery. This study aims to determine learning outcomes before using the inquiry strategy in science subjects with environmental change material and learning outcomes after using the inquiry strategy in science subjects with environmental change material and applying the inquiry strategy in science subjects with environmental change material. This type of research is classroom action research with class IV A research subjects consisting of 24 students and the instruments used are tests, observations/observations and documentation. Data collection techniques with observation sheets for students and teachers. Data analysis techniques with data reduction, and data presentation. The results of this study were that during the pre-cycle of the 24 students the level of completeness in this pre-cycle was only 41.66%. At the time of implementation of Cycle I, it was given in the form of learning using a strategy, it was known that student learning outcomes in cycle I on science subject matter had increased compared to the results of the pre-test. However, the results of the written test have not reached completeness and are still relatively low with an average of 66.66%. And in Cycle II it increased by an average of 83.33%.